Predicting throwing performance with force-velocity mechanical properties of the upper limb in experienced handball players - Zhang, Q.; Gassier, R.; Eymard, N.; Pommel, F.; Berthier, P.; Rahmani, A.; Hautier, C. A. (Journal of Human Kinetics, 2025)
This study investigated the relationship between force-power-velocity (F-P-V) mechanical variables measured during the ballistic bench press throw (BPT), shoulder isokinetic rotation strength, and the throwing velocity in handball players. Twenty-seven experienced male handball players (age: 20.0 ± 3.2 yrs, body height: 180.5 ± 6.3 cm, body mass: 73.9 ± 7.9 kg) volunteered for the investigation. F-P-V mechanical variables (i.e., theoretical maximal force [F0], velocity [V0], power [Pmax]) were obtained during the single-arm BPT and an isokinetic shoulder isokinetic internal rotation test. Throwing performance was assessed for the standing and 3-step throwing velocity. Participants were divided into a "High/Fast" and a "Low/Slow" group considering their throwing performance based on a median split analysis. A strong correlation was found between V0 obtained from the BPT and maximal throwing velocity for standing throwing (r2 = 0.51, f2 = 1.04) and three-step throwing (r2 = 0.46, f2 = 0.85). At the same time, Pmax obtained from the BPT had a weak association with three-step throwing performance (r2 = 0.18, f2 = 0.22). Furthermore, no significant correlation was found between all the mechanical variables obtained from the isokinetic rotation and throwing performance (all p-values > 0.05). The High/Fast group showed that only V0 and Pmax obtained from the ballistic BPT had a small to moderate effect size (ES [0.06 0.23]) compared to the Low/Slow group. This finding indicates the importance of measuring the upper limb F-P-V profile obtained from the BPT in predicting throwing performance. Thus, training programs should focus on F-P-V mechanical properties to design specific training methods to optimize throwing performance in handball players.